Introduction of the modern physician and the debate on medical professionalism in the 19th-Century Ottoman Empire - Rasimoglu, Ceren Gulser Ilikan (EDITORIAL UNIV GRANADA, 2021)
This article focuses on how boundaries were created between modern physicians and traditional healers when the modern medical profession was established in the 19th century Ottoman Empire, based on documents from the Ottoman Archives of the Prime Minister???s Office. In the Tanzimat period (1839-1 876), the Ottoman elites focused on modifying the education system with the aim of modernizing the institutions of the Empire, and medical education was one of their priorities. The Imperial School of Medicine was inaugurated in 1839, and a series of regulations simultaneously established that only graduates from the modern schools had the right to practice medicine. These regulations detailed the content of the education, the stages to be completed in order to graduate, and the regulation of professional praxis post graduation. These regulations drew a boundary between the professional and the layman. Their aim was to achieve the domination of certified professionals over the health field, expelling non-professionals once enough staff became available. The article examines the rivalry between modern and traditional physicians and the diverse strategies employed to distinguish between modern and lay practitioners and to deny legitimacy for some medical practices. The panorama was further complicated by the ethnicity factor in the context of unrest in the Empire at that time. Other questions addressed in this text include: What discourses and legal regulations played a role in forming the boundaries between customary and modern educational processes? How did the Ottoman elites seek to control the population through medicine and health policies?
Keywords: medical fraud; charlatans; medical professionalization; Late Ottoman Empire; Ottoman medicine